Alternatif Dasar Perhitungan Nilai Tanah untuk Pembangunan Waduk - Suriadi, Andi (Jurnal Sosial Ekonomi Pekerjaan Umum, 2013)
Recently, one of the problems that hinder dam development is land acquisition. Some landowners are reluctant to give up their land to the compensation values offered by Land Supply Committee. The landowners often demand higher price than the platform, but there is no strong legal basis to pay higher than the platform. Whereas the existing land price calculation model is mainly based on tangible aspects (taxes, distance, area, function, slope, and condition), lands also hold intangible values for the owners. This research use qualitative method, conducted in four locations: Karian dam, Batutegi dam, Sermo dam, and Jatibarang dam. The research shows three important intagible variables in socio-cultural aspect, namely magical-religious value, ways to own the land, and the duration of ownership. The variables could be accomodated in calculation of land price. The alternative variables address both various characteristics of land price and landowners’ expectation more objectively and accountably. Therefore, the role of land brokers which often exaggerate the land price could be minimized and consequently, in the future, land acquisition will no longer be a dominant issue hampering dam development.